Business Plan : Ku Anis Cake & Bakery / Nuraida Syamimi Mohd Azuki…[et al.] - Mohd Azuki, Nuraida Syamimi; Zakaria, Sofea Qistina; Nik Man, Nik Nurnina Anis Alya; Abdul Rahim, Siti Nur Atirah (2021)
This business plan was prepared based on the case study and business opportunity that we had finished it previously. According to the business plan requirement, this business is based on partnership where it consists of five (5) members that hold important positions in the company such as General Manager, Administrative Manager, Marketing Manager, Operation Manager and Financial Manager. The business capital is amounted to RM 250,000 which is from the total contribution of each member is RM20,000 and the rest is RM150,000 from Bank Islam’s Loan. Ku Anis Cake & Bakery is base in Kelantan that located at Lot 1823, Kampung Wakaf Mek Zainab, Daerah Panji Mukim Tanjung Chat, 15300 Kota Bharu, Ku Anis Cake & Bakey is a business that focuses on customer service, baking and decorating cakes and also delivering orders. Generally, everyone loves cake. Because of that, cake is one of the most well known products in our business. Usually, people serves cake in many event such as birthday celebration, anniversary celebration, retirement celebration, wedding and so on. In addition, to make it more creative and innovative, we decided to make some innovation on our products. As we know, a cake is a form of sweet food that made from flour, sugar, and other ingredients. So that, we decided to make it more healthy instead of an ordinary sweet dessert. In this business plan, we will provide more about our business such as business description, partners description, administration plan, marketing plan, operational plan and financial plan. Hopefully, by preparing this business plan and using the fund from Bank Islam’s loan, we can achieve what we actually want to do for our business and we can survive from any challenges in future.